2023
DOI: 10.1136/rapm-2022-104117
|View full text |Cite
|
Sign up to set email alerts
|

Pericapsular nerve group (PENG) block for early pain management of elderly patients with hip fracture: a single-center double-blind randomized controlled trial

Abstract: BackgroundThe pericapsular nerve group block (PENG) is a novel technique that blocks the articular branches of the hip joint. This study aimed to compare its effectiveness to a sham block in elderly patients with hip fractures.MethodA randomized double-blind controlled trial was conducted in elderly patients with intertrochanteric and neck of femur fractures. Patients were randomized to receive either PENG block or a sham block. Postblock, systemic analgesia was titrated using a standardized protocol of acetam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The PENG block was effective for pain control even in the preoperative period (in the 24 h following the trauma) as a purely antalgic strategy for hip fracture patients. Xufeng et al have shown that this technique reduces the median NRS score by three points and lessens morphine use highlighting, the greater safety of this technique and suggesting that it could also be an elective technique for hip fracture patients planned for conservative treatment [49] .…”
Section: Discussionmentioning
confidence: 98%
“…The PENG block was effective for pain control even in the preoperative period (in the 24 h following the trauma) as a purely antalgic strategy for hip fracture patients. Xufeng et al have shown that this technique reduces the median NRS score by three points and lessens morphine use highlighting, the greater safety of this technique and suggesting that it could also be an elective technique for hip fracture patients planned for conservative treatment [49] .…”
Section: Discussionmentioning
confidence: 98%
“…The utilization of ultrasound-guided PENG block as an approach to providing perioperative analgesia to patients undergoing hip surgery is becoming increasingly common [ 9 , 10 ]. While PENG block can yield satisfactory analgesic efficacy, it also has the potential to block the function of the femoral nerve [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of the PENG block in various studies has shown its superior analgesic effectiveness in lowering opioid consumption, decreasing the incidence of motor blockade, and shortening discharge time as compared to patients with no nerve block, a femoral nerve block, and an infra-inguinal fascia iliaca block with hip fractures [ 23 , 25 , 26 , 27 ]. In a single-center, double-blind, randomized controlled trial performed by Lin, Xufeng et al in Singapore General Hospital, they found that the PENG block was superior to a sham block at reducing acute traumatic pain at 30 min ( p < 0.01) and 3 h post block ( p < 0.05) and reducing opioid consumption ( p < 0.05) following hip fracture [ 28 ]. Although a PENG block is good at providing analgesia, it cannot be used as the sole anesthetic for hip surgery.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%